Zulu [videorecording (DVD)] - Endfield, Cy, 1914-1995; Endfield, Cy, 1914-1995; Endfield, Cy, 1914-1995; Baker, Stanley, Sir, 1928-1976; Caine, Michael; Hawkins, Jack, 1910-1973 (MGM DVD., 2003)
In 1879, British soldiers in colonial South Africa, despite advice by a preacher to give up the outpost, decide to defend their encampment with a force of 105 men against 4,000 Zulus.